Effect of Hot Chair Strategy on the Acquisition of Second-Grade Middle Class Students - Faris Yousif, Jehan; Mahmood, Read Idrees (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of the research was to identify the impact of the hot chair strategy on the acquisition of second grade intermediate students of the concepts and the development of the chemical survey and their higher thinking skills. The researchers adopted the experimental design of the two equal groups. The research community determines the average second grade students in the secondary schools in Tikrit for the academic year 2018 -2019, a high school was chosen for girls as a sample. Of a total of 69 students, 34 of the experimental group studied in accordance with the hot chair strategy and 35 students in control group studied the usual way. The researchers compared the two groups in the variables: grades of chemistry for the past year, age calculated by months, academic achievement of the parents of the students, degree of the chemical survey and higher thinking skills. The results showed that there was a superior difference between the students of the experimental group who studied according to the hot chair strategy on the female students of the control group, which studied according to the usual method.